A contemporary fashion criticism model based on formative research methodology: an empirical study - Park, Sujin; Ha, Jisoo (Fashion and textiles, 2025)
Previous studies on fashion criticism have predominantly focused on theoretical reviews, offering limited practical methodologies for engaging in fashion criticism. To address this gap, the primary objective of this study is to propose and empirically validate a contemporary fashion criticism model that bridges the divide between theoretical understanding and practical application. Two research questions are addressed: First, what are the essential elements of a contemporary fashion criticism model that differentiate it from traditional art criticism? Second, what factors are necessary to ensure that a contemporary fashion criticism model is grounded in practical relevance? The study employed formative research to develop and validate the model. A basic model was initially constructed using basic and supplementary elements derived from art criticism models. The proposed model then underwent multiple rounds of internal and external validation by eight experts. The Content Validity Index and Inter-Rater Agreement were used to assess content validity, while external validation was conducted through the experimental application of the developed model in critiquing fashion objects and in-depth interviews. The finalized model consists of 7 procedures and 14 detailed criteria, all confirmed for validity and reliability. This model integrates diverse perspectives on contemporary fashion criticism, reflecting its “situationality,” which contrasts the relatively static nature of art criticism. It serves as a valuable and versatile tool for objectively assessing contemporary fashion, providing a foundational benchmark for experts and broader audiences alike.